Teachers’ well-being and their teaching quality during the COVID-19 pandemic: a retrospective study - Sacré, Margault; Ries, Nora; Wolf, Kristin; Kunter, Mareike (Frontiers in Education, 2023)
During the COVID-19 pandemic, teachers reported low levels of well-being. Lower levels of well-being can negatively impact job performance and teaching quality. This study aims to examine whether the quality of teaching changed between before and during the pandemic, in two settings: remote and restricted in-person settings, and whether teachers’ well-being was related to the quality of teaching. 279 German-speaking (primary and secondary) teachers were retrospectively surveyed with an online questionnaire. Results showed that even if teachers reported being emotionally exhausted, they still were satisfied with their profession, highlighting the multidimensionality of well-being. For online instruction, teachers reported decrease in teaching quality in terms of cognitive activation, classroom management, and learning support compared to pre-pandemic times. Additionally, according to the teachers, their teaching quality did not return to its original state when schools reopened. However, the data does not show that this decrease is associated with teachers’ well-being. This study suggests that it is not only the quantity of learning that may have caused students’ learning losses, but also its quality. As a possible practical consequence, it seems helpful to provide teachers not only with technical, put also pedagogical support when teaching online and after having returned to in-person settings.